2017
DOI: 10.1021/acs.jpcc.7b00003
|View full text |Cite
|
Sign up to set email alerts
|

Simple-to-Apply Wetting Model to Predict Thermodynamically Stable and Metastable Contact Angles on Textured/Rough/Patterned Surfaces

Abstract: Rough/patterned/textured surfaces with nano/microcavities that broaden below the surfaceknown as "re-entrants"can be omniphobic (macroscopic contact angle greater than 90°for both water and oils). The existing theoretical models that explain the effects of texture on wetting are complex and do not provide a simple procedure for predicting the thermodynamically stable and metastable states and their corresponding contact angles (for example, wetting states that involve partially filled cavities). Here, we dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
72
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 61 publications
3
72
0
1
Order By: Relevance
“…Below we explain the mechanisms underlying the contrasting behaviors of silica surfaces with DRPs and DRCs on immersion. It has been demonstrated that doubly reentrant features, pillars or cavities, can stabilize sessile drops due to their geometry, such that if the drops were pushed into the microtexture the curvature at the solid-liquid-vapor interface resisted penetration (Figure 4 inset) [20,24,27,28]. In fact, the concave curvature of the liquid meniscus gave rise to capillary pressure, also known as the 'Laplace pressure', that prevented the imbibition and has the following general expression , where is the surface tension of the liquid, θ o is the intrinsic contact angle at the solid-liquid-vapor interface at thermodynamic Omniphobic Omniphobic equilibrium, and is the mean curvature of liquid-vapor interface, and R 1, R 2 the two mutually orthogonal radii of curvatures of the liquid-vapor interface [33].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Below we explain the mechanisms underlying the contrasting behaviors of silica surfaces with DRPs and DRCs on immersion. It has been demonstrated that doubly reentrant features, pillars or cavities, can stabilize sessile drops due to their geometry, such that if the drops were pushed into the microtexture the curvature at the solid-liquid-vapor interface resisted penetration (Figure 4 inset) [20,24,27,28]. In fact, the concave curvature of the liquid meniscus gave rise to capillary pressure, also known as the 'Laplace pressure', that prevented the imbibition and has the following general expression , where is the surface tension of the liquid, θ o is the intrinsic contact angle at the solid-liquid-vapor interface at thermodynamic Omniphobic Omniphobic equilibrium, and is the mean curvature of liquid-vapor interface, and R 1, R 2 the two mutually orthogonal radii of curvatures of the liquid-vapor interface [33].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the thermodynamically stable fully-filled (Wenzel) state could be delayed [27] . The same liquid, however, infiltrates the microtexture from the boundary, a surrogate for localized defects (right corner).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, if the inlets and outlets of the pores have reentrant profiles (e.g., "T"-shaped), they may prevent the wetting liquid from penetrating the pore and entrap air inside, leading to Cassie states 33 ( Figure 1C,D). Once the air is trapped inside the pore, it will further prevent liquid intrusion due to its compressibility and low solubility in water over time 34,35 .…”
Section: Introductionmentioning
confidence: 99%
“…Such a system will slowly transition from Cassie to Wenzel state, and the kinetics of this process can be tuned by the pore's shape, size, and profile, vapor pressure of the liquid, and solubility of the trapped air in the liquid 29,34,36 . Researchers have been able to realize GEMs using silicon wafers and polymethylmethacrylate sheets as the test substrates, and proof-of-concept applications for DCMD in a cross-flow configuration have been demonstrated 37 .…”
Section: Introductionmentioning
confidence: 99%